CURRENT ISSUES OF TEACHING NATURAL SCIENCES IN MODERN EDUCATION - Avazbekova, Shakhsanam Nurmamat qizi (Educational Research in Universal Sciences, 2023)
In this article, the current issues of teaching Natural Sciences in the direction of primary education, pedagogical approaches to the use of pedagogical technologies in teaching science, mechanisms for the use of educational tools, natural sciences are covered by educational goals organized in series within the Department.